Develop and design of personal development tool ( SSB MINDSPA 2.0 ) using quality function deployment procedure - Muhammad Syamil Bin Mohd Sabri (2023)
Stress is a normal reaction for a person when they feel too much pressure on them. Sometimes stress can be a good cause for a person to be productive but overstress is dangerous as it can leads to some serious disorder such as depression and anxiety. This project was initiated solely for that purpose and with other objectives. First objective is to design a personal development tool which is SSB MINDSPA 2.0 for stress management. Second objective is to blend therapies into the personal development tool such as Neuro-Linguistic Programming (NLP), Brainwaves, Perfect Breathing, Hypnosis, and others. The last objective is to verify the effectiveness of the device by collecting sample of data. This personal development tool was designed by using Quality Function Deployment procedure which is a very common type of design method in any industry. After fabricating the prototype, testing was conducted and sample of data was collected. One of the data is the result of percentage of body fat of a respondent before and after using the personal development tool and the result was satisfying as the body fat percentage was decreased from 29.1% to 28.4%. After analysis of the results, it can be concluded that SSB MINDSPA 2.0 is effective in managing stress.